Proceso de atención de enfermería en gestante adolescente de 17 años de 32 semana, con anemia ferropenica. - Guzmán Lema, Cristhian Hernán (2020)
In the course of the pregnancy process, several types of anemia can be verified, among which the one that stands out is iron deficiency anemia, since with 80% in pregnant women, the development of said disease is caused by the decrease in hemoglobin levels present in the blood (less than 11g / dl). Health training is essential through this knowledge you can reprimand this disease and the discomfort it can cause during the gestation period. Basing the proposal that will be guided by developing a nursing care plan in this way could meet the needs of the user and serve as a guide to arrange the most optimal activities to perform to restore the health of the patient and the fetus. Providing information as a nursing professional by having as a clear theoretical basis to define, know and treat the inconvenience that the pregnant woman already mentioned above presents is of great importance not only for the user but also as training for the health professional indicating every detail about the activity you must do. Ingesting an excellent balanced diet that includes carbohydrates, fats, proteins will help in an essential way that the fetus has adequate growth and development during the gestation period in this way during the course of the childbirth process so that significant complications cannot occur. compromise the integrity of both the mother and the fetus during childbirth.